Numerical computation of low Reynolds number viscous flow past bluff bodies - Tarafder, Md. Shahjada; Mursaline, Miad Al (Zielona Góra: Uniwersytet Zielonogórski)
This article presents a two-dimensional steady viscous flow simulation past circular and square cylinders at low Reynolds numbers (based on the diameter) by the finite volume method with a non-orthogonal body-fitted grid. Diffusive fluxes are discretized using central differencing scheme, and for convective fluxes upwind and central differencing schemes are blended using a "deferred correction" approach.
Keywords: viscous flow; low Reynold`s numbers; SIMPLE algorithm; circular and square cylinder; drag coefficient